2002
DOI: 10.1124/dmd.30.11.1274
|View full text |Cite
|
Sign up to set email alerts
|

Biotransformation of Mirtazapine byCunninghamella Elegans

Abstract: ABSTRACT:The fungus Cunninghamella elegans was used as a microbial model of mammalian metabolism to biotransform the tetracyclic antidepressant drug mirtazapine, which is manufactured as a racemic mixture of R(؊)-and S(؉)-enantiomers. In 168 h, C. elegans transformed 91% of the drug into the following seven metabolites: 8-hydroxymirtazapine, N-desmethyl-8-hydroxymirtazapine, N-desmethylmirtazapine, 13-hydroxymirtazapine, mirtazapine N-oxide, 12-hydroxymirtazapine, and N-desmethyl-13-hydroxymirtazapine. Circula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
28
1
7

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 19 publications
5
28
1
7
Order By: Relevance
“…A major goal of studies on these microbial models is to develop a list of microorganisms that can mimic the metabolic profiles of drugs in mammals. Filamentous fungi from the genus Cunninghamella, particularly Cunninghamella elegans, often metabolize drugs in a manner similar to that in mammals (2,3,7,10,11,15,22).…”
Section: Verapamil ␣-[3-[[2-(34-dimethoxyphenyl)ethyl]methylamino]mentioning
confidence: 99%
See 1 more Smart Citation
“…A major goal of studies on these microbial models is to develop a list of microorganisms that can mimic the metabolic profiles of drugs in mammals. Filamentous fungi from the genus Cunninghamella, particularly Cunninghamella elegans, often metabolize drugs in a manner similar to that in mammals (2,3,7,10,11,15,22).…”
Section: Verapamil ␣-[3-[[2-(34-dimethoxyphenyl)ethyl]methylamino]mentioning
confidence: 99%
“…A major goal of studies on these microbial models is to develop a list of microorganisms that can mimic the metabolic profiles of drugs in mammals. Filamentous fungi from the genus Cunninghamella, particularly Cunninghamella elegans, often metabolize drugs in a manner similar to that in mammals (2,3,7,10,11,15,22).Although the metabolism of verapamil in mammals has been studied, little is known about the potential of nonligninolytic fungi to metabolize verapmil. The objective of this paper is to identify a fungus that can extensively metabolize verapamil and to chemically identify the metabolites.…”
mentioning
confidence: 99%
“…C. elegans DSM 1908 is well known as a model of mammalian drug metabolism (10,11), and analysis of the organically extractable metabolites by 19 F NMR spectroscopy using a Varian 400-MHz spectrometer revealed that flurbiprofen was completely degraded to one fluorometabolite over 3 days (Fig. 1).…”
mentioning
confidence: 99%
“…Work in this area has been reviewed (Abourashed et al, 1999;Azerad, 1999), and there has been an increasing number of reports describing the use of microbial systems to mimic or predict mammalian metabolite formation and to prepare larger quantities of mammalian metabolites (Moody et al, 1999(Moody et al, , 2002Xie et al, 2005;Zhang et al, 2006;Zmijewski et al, 2006). The traditional microbial screening methods using shake flasks are labor intensive, which has likely limited the widespread use of microbial biotransformation in drug metabolism studies.…”
mentioning
confidence: 99%